Regeneration of Shorea robusta Gaertn. (Sal) by Seed Sowing Method - an Experiment Done in Sarguja District, Chhattisgarh - Sharma, J. P.; Nonhare, B. P. (Indian Forester, 2004)
Sal forests in our country are depleting due to various reasons. Sal forests are very important not only for timber but for maintaining biodiversity. Sal regeneration has always been a problem throughout the country. The paper discusses the result of regeneration trial of Sal carried out in South Sarguja Forest Division (Chilattisgarh) in 1985. The result of the trial indicates that seed broadcast in well ploughed soil immediately after seed fall in well protected area gives profuse regeneration. Seedlings were spaced out in second year by removing congested seedlings. The maximum height attained in thirteenth year of sowing is 13m and girth at breast height 61cm. If the adverse factors e.g. grazing, fire and hardness of soil are eliminated, profuse regeneration and subsequent establishment of sal is obtained. In Sal areas where regeneration is lacking, this technique of regeneration can be fruitful with providing strict protection to the area concerned.